Factors Contributing to Buying Interest (Study on Yakult Product Consumers in Solo City) - Badruzzaman, Muhammad; Widyaningsih, Dewi; Sumarlin, Tantik (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: The purpose of this study is to determine and examine how field selling tactics, brand perception, customer experience, and social media directly affect consumers' desire to purchase Yakult products in Solo. Methodology/approach: This study employs a quantitative methodology and a survey approach with a questionnaire for data collecting. Purposive sampling was utilized in the sample withdrawal procedure, and 100 respondents who bought Yakult products in Solo were included in the sample. IBM SPSS Statistics 25 was used to analyze the data using multiple linear regression analysis tests. Results/findings: The study found that field selling strategy, brand image, customer experience, and social media each have a significant positive effect on consumer purchase interest in Yakult products. Additionally, these variables collectively influence buying interest in a significant and positive manner.Conclusions: It can be concluded that all four factors—field selling, brand image, customer experience, and social media—play an important role in increasing consumer buying interest. An integrated marketing approach that focuses on these aspects can effectively boost consumer intention to purchase Yakult in Solo. Limitations: Determinants of interest in buying Yakult products, such as field selling strategies, brand image, customer experience, and social media, affect an individual's repurchase interest, even though there are health drink products other than Yakult. Contribution: In this study, it is intended to be able to understand the perceptions and preferences of Generation Z to enable companies to develop effective marketing strategies, strengthen brand image, and increase competitiveness in the market.